Analisis Harga Saham: Bukti Empiris pada Sub Sektor Kontruksi Bangunan di Bursa Efek Indonesia - Muhammad Riza Saifullah; Rahman Amrullah Suwaidi (Universitas Batanghari Jambi, 2023)
The share price is the prevailing price on the stock exchange at a certain time. The findings from this study will help to ascertain whether Profitability, Liquidity, Solvency can contribute to the Stock Price of the Building Construction industry sub-sector on the Stock Exchange. There were 19 industries selected by applying purposive sampling technique. The findings of the study will be tested coming from secondary information, particularly the annual financial reports of the Indonesia Stock Exchange and panel information. Data analysis methods to validate hypothesis data include descriptive testing, classical assumption testing, and hypothesis testing using multiple linear regression analysis with the SPSS v25 program. The study findings prove (1) Profitability using a net profit margin proxy or net profit margin does not contribute to the building construction industry stock price on the Indonesia Stock Exchange; (2) Liquidity by proxy current ratio or current ratio cannot contribute to the building construction industry stock price on the Indonesia Stock Exchange; (3) Solvability by proxy debt to equity ratio or debt to equity ratio contributes to the share price of the building construction industry on the Indonesia Stock Exchange.